LABOR CONDITIONS AND LABOR SATISFACTION PHYSICAL EDUCATION TEACHERS (Fiep Bulletin - online, 2014)
In this work we study the quality of life of 287 teachers of Physical Education, both gender, between 21 and more than 60 years, who work in different places of  Buenos Aires Conurban and Buenos Aires City , to know their work conditions and level of labor satisfaction. This research project was developed between 2005 - 2006 in the context of the National Program of Incentives for researchers-professors of the National Ministry of Education and in it have worked researches from the Quality of Life Research Program of the Social Sciences Faculty, Lomas de Zamora National University and from the Physical Education career, of La Matanza University. We use the theoretical view of Quality of Life witch remits to the material environment and the psycho social environment , being defined as a concept witch implies two axis : the objective and the subjective ( Tonon, 2003 ). We will say that the relation between the two concepts: Physical Education and Quality of Lifeforms an interdisciplinary and multidimensional view to take into account for the daily putting in motion of teachers of the area and it is for that, that we also study the measurement of the quality of life of this population. This article presents the first conclusions that come out from the data analysis and try to explain them in their context of development.
Keywords: Physical Education; Quality of Life; Labor Satisfaction